ADRENOMEDULIN DI KARSINOMA PAYUDARA DENGAN METASTASIS - Stefanus Lembar (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2015)
Metastasis is the leading cause of mortality in patients with breast cancer. The molecular biology behind the metastasis is verycomplex and may require changes in the regulation of the cell cycle, protein that promotes autocrine growth loop, and the protein thatcauses epithelial to mesenchymal transition. More complex, it is clear that the biology of metastasis is partly governed by the non-tumourcells, including fibroblasts, endothelial cells and myoepithelial cells. Adrenomedullin is an autocrine growth factor produced by the renalcarcinoma cells. However, previous studies indicated that adrenomedullin can be secreted in various carcinoma tissue and carcinoma cells.Adrenomedullin may mediate immunosuppression, antiapoptosis, angiogenesis and proliferation, thus it is an important tumour cellsurvival factor underlying human carcinoma genesis. The role of adrenomedullin in the carcinoma genesis, invasion and metastasis hasbeen greatly focused. The aim of this study was to determine the concentration of adrenomedullin in patients with metastatic breast cancer.A total of 64 patients with breast cancer aged 21–90 years (63 women and 1 man) in Jakarta has been participated in this study aftersigning informed consent. Metastasis was confirmed by examination of bone scanning. Concentrations of adrenomedullin were measuredby EnzymeLinked Immunosorbent Assay (ELISA) using a commercial kit. Based on examination of bone scanning, there were 24 (37.5%)subjects with metastasis and 40 (62.5%) nonmetastasis. Mean of the concentrations of adrenomedullin in the subjects with metastasiswas 252.5 (205.0–299.9) pg/mL, while in the nonmetastasis was 203.1 (178.7–227.5) pg/mL. The concentrations of adrenomedullinwere significantly higher in subjects with metastasis than nonmetastasis (p=0.041). High concentration of adrenomedullin in the subjectswith metastasis suggests that adrenomedullin may be more likely to be involved in metastasis.